Green Nourishment: An Innovative Nature-Based Solution for Coastal Erosion - Chen, Wen L.; Muller, Peter; Grabowski, Robert C.; Dodd, Nicholas (Frontiers in Marine Science, 2022)
Coastal erosion poses an urgent threat to life and property in low-lying regions. Sand nourishment is increasingly used as a nature-based solution but requires significant natural resources and replenishment over time. In this study, a novel form of nourishment is explored that combines shoreface nourishment and seagrass restoration to mitigate coastal erosion (i.e., green nourishment). Using the coastal morphodynamic model Xbeach, the impact of seagrass planting on wave energy dissipation, sediment erosion and transport, and morphological evolution of a cross-shore profile was studied for mild wave conditions and an intense storm. Model results indicate that a seagrass meadow enhances the wave energy dissipation provided by a shoreface nourishment, and suggests that it may be particularly effective in sediment transport mitigation when implemented in a sheltered nearshore area. The shoreface nourishment reduced the wave height on the seagrass meadow, and reduced the rate of seagrass destruction by deposition or erosion above the grass height after the storm event. Green nourishment also reduced beach foreshore erosion caused by a simulated storm event. An alternative, more cost-effective planting technique using seagrass seeds was explored, which showed similar coastal erosion protection benefits for seagrass transplants. This modeling study found that green nourishment is potentially an effective nature-based solution for coastal erosion and flooding on sandy coasts, and future studies are recommended to evaluate its morphological, ecological and flood risk reduction benefits in the field.